PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN 364 CEPPAGA KECAMATAN TAKKALALLA KABUPATEN WAJO - Abd. Hafid ,; Sudarto,; Fira Yunengsi , (JOEL: Journal of Educational and Language Research, 2024)
This research is a Classroom Action Research (CAR) which aimed to improve the Indonesian Language learning outcomes of the 5th Grade students at SDN 364 Ceppaga, Takkalalla District, Wajo Regency. The subjects of this research were all of the 5th Grade students. Data collection techniques use a test list. The data analysis technique is a descriptive statistical data analysis. Research results: the average student score in cycle I was 67.69 (in the sufficient category) and in cycle II was 78.15 (in the good category). The conclusion of this research is that the STAD type cooperative learning model can improve Indonesian Language learning outcomes for the 5th Grade students at SDN 364 Ceppaga, Takkalalla District, Wajo Regency